PENGEMBANGAN BAHAN AJAR KONTEKSTUAL UNTUK MATA PELAJARAN IPS SEKOLAH DASAR - Lestari, Citra Dwi (Perspektif Ilmu Pendidikan, 2016)
This research and development aimed at producing social science learning materials for the fourth grade of Elementary School students. The learning materials contain economic activities related to natural resources and other potentials in their area. This research used research and development method with reference to the instructional development model adopted by Atwi Suparman. This research involved the fourth grade students in Binong V Primary School, Tangerang Regency. This research used questionnair, observation, and interview to collect data from the respondent. The steps included experts review, one to one evaluation, small group evaluation, and field test. The results indicate that the development of social science learning materials based on contextual approach reach the very good criteria.